The relationship of salivary cortisol and Volatile Sulfur Compounds with Halitosis among pregnant woman - Mareim Radhi Abd Al Nabby / Abbas Almizraqchi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Halitosis, commonly known as bad breath, significantly impacts an individual’s social life, self-esteem, and overall quality of life. While local oral factors predominantly cause halitosis, systemic conditions and hormonal changes, especially during pregnancy, can also influence its occurrence. Conducted at Al-Sader Teaching Hospital in Missan, Iraq, from October 2023 to February 2024, this cross-sectional study involved ninety female participants, divided equally into a patient group of pregnant women aged 20 to 40 years suffering from halitosis and a healthy control group of non-pregnant women. The study meticulously adhered to inclusion and exclusion criteria to ensure a focused and relevant participant pool. Measurements of VSCs and salivary cortisol levels were undertaken using standardized methods and advanced technology. The study found a significant elevation in the levels of cortisol and VSCs among the pregnant group compared to the control group, suggesting that pregnancy-induced hormonal changes and stress response could contribute to or exacerbate conditions leading to halitosis. Elevated cortisol levels and VSCs in pregnant women underscore the multifaceted relationship between pregnancy, hormonal changes, stress, and oral health, particularly concerning halitosis.